The Influence of Situational Leadership Style on Teacher Performance (Case Study at SMK Cahaya Surya) - Puspitaningrum, Yuliawati; Arisyahidin, Arisyahidin; R, Deby Santyo (Syntax Corporation, 2025)
Education plays a crucial role in developing high-quality human resources, where teacher performance is a key factor in the success of learning. One aspect that influences teacher performance is the principal's leadership style. Situational leadership is considered effective as it can adapt its approach to the needs of teachers. However, at SMK Cahaya Surya Kota Kediri, challenges were found in the work environment and the suboptimal implementation of situational leadership. Therefore, this study aims to analyze the influence of situational leadership style on teacher performance to enhance leadership effectiveness in schools. This research employs a quantitative approach with a descriptive design. The study was conducted at SMK Cahaya Surya, Kota Kediri, with a population of 100 teachers from Yayasan Surya Dharma Laksana. The sampling technique used was non-probability sampling, specifically convenience sampling, with the sample size determined using the Slovin formula at a 5% margin of error. Data were collected through observation, questionnaires, documentation, and literature review. Data analysis included the Likert scale, validity and reliability tests, classical assumption tests (normality, linearity, heteroscedasticity), multiple linear regression, as well as t-tests, f-tests, and the coefficient of determination (R²) to examine the relationships between variables. The study concludes that situational leadership style significantly influences teacher performance at SMK Cahaya Surya Kota Kediri, with a beta coefficient of 39.4%. Effective principal leadership can optimize teacher performance, aligning with previous findings that emphasize the crucial role of leadership in enhancing teacher performance. Keywords: Leadership effectiveness, situational leadership style, teacher performance